Morphometric and Meristic Characteristics of Walking Snakehead Channa Orientalis in a Wetland Ecosystem (Northwestern Bangladesh) Using Multi-Linear Dimensions (Journal of Bio-Science, 2021)
The present study is illustrated complete morphometric and meristic characteristics of fresh water fish, walking snakehead, Channa orientalis (Bloch & Schneider 1801), using nine linear dimensions and covering different fin-rays (i.e., dorsal fin, D; pectoral fin, P1; pelvic fin, P2; anal fin, A and caudal fin,C) from the wetland ecosystem Gajnar Beel in northwestern (NW) Bangladesh. Total 230 specimens of C. orientalis were collected from the Gajnar Beel in the time of January to December 2018 by several local fishing gears (e.g., cast net, gill net and square lift net (mesh size ranges: 1.5 - 2.5 cm, 1.5 - 2.0 cm, & ~2.0 cm, respectively). Different morphometric lengths were measured to 0.01 cm, and whole body weight (BW) was estimated 0.01 g for each individual. Fin rays and scales (including lateral line scale) were computed by a magnifying glass. All LWRs were highly significant (p